Electronic portfolio-based learning development training for Teachers of SMP Muhammadiyah 3 Yogyakarta - Ali, Raden Muhammad; Hastuti, Dwi; Biddinika, Muhammad Kunta; Pamungkas , Rani Rahmawati; Alfaridhi, Dio Fahmi; Syahputra, Derly; Putri, Anggista Malya; Mbuo, Wilda; Nadia, Hafizhatu (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
The world of education needs to keep up with the development of information technology in providing learning services for students. One of the tools that is currently widely known for its advantages and widely used in developed countries is the electronic portfolio. The background of this program is a problem that is often faced by schools, namely the lack of teacher competence in developing learning by utilizing electronic portfolios in teaching. SMP Muhammadiyah 3 Yogyakarta (SMP Muhammadiyah 3 Yogyakarta), as one of the private schools in Yogyakarta that has a high concern for the application of information technology in learning, in collaboration with the Community Service Team of Ahmad Dahlan University carried out an electronic portfolio-based learning development training which was attended by teachers of various subjects and education staff who served in various school service units. The objective of this activity is to improve teachers' understanding and skills by using electronic portfolios to support the realization of quality learning. The methods used are training and mentoring for teachers to develop electronic portfolio- based learning, improving internet infrastructure, and monitoring and evaluation. This training has resulted in an increase in the trainees' understanding of the concept of electronic portfolios and the improvement of participants' skills as shown by a total of 43 participants who have been able to develop their electronic portfolios. To ensure the implementation of electronic portfolios in schools, the Principal has decided that six classes with IT (Information Technology) specialization consisting of two learning groups from Grade 7, Grade 8, and Grade 9 will implement electronic portfolio-based learning. The impact of this training is that teachers have a positive mindset towards the use of information technology so that it further increases the opportunity for schools to improve the quality of learning in accordance with technological developments.